Evaluation of outpatient discharge in patients with cutaneous melanoma - Nurimar C. Fernandes; Flauberto de Sousa Marinho (Revista do Colégio Brasileiro de Cirurgiões)
OBJECTIVE: to evaluate discharge in a group of patients with cutaneous melanoma according to recently established criteria. METHODS: we conducted an observational, cross-sectional study with 32 patients at the Hospital Universitário Clementino Fraga Filho (HUCFF) / Universidade Federal do Rio de Janeiro (UFRJ), between 1995 and 2013, in the following stages: IA (17 cases, 53.12%), IB (4 cases, 12.5%), IIA (3 cases, 9.37%), IIC (1 case, 3.12%), IIIB (1 case, 3.12%), IIIC (3 cases, 9.37%), melanomas in situ (2 cases, 6.25%), Tx (1 case, 3.12%). RESULTS: the follow-up time varied from one to 20 years (stage IA), five to 15 years (stage IB), six to 17 years (stage IIA), 20 years (stage IIC), 23 years (stage IIIB) and 14 to 18 years (stage IIIC). One melanoma in situ (subungueal) was discharged in the fourth year of follow-up and the other was promptly discharged. The Tx melanoma was followed for 12 years. We observed no relapses or recurrences in the period. CONCLUSION: although a controversial issue, it was possible to endorse the discharge of the patients since our follow-up time had already exceeded the one recommended by the other authors.